Cellulose nanocrystals with tunable surface charge for nanomedicine. Issue 40 (8th July 2015) - Hosseinidoust, Zeinab; Alam, Md Nur; Sim, Goeun; Tufenkji, Nathalie; van de Ven, Theo G. M.
Abstract : Crystalline nanoparticles of cellulose exhibit attractive properties as nanoscale carriers for bioactive molecules in nanobiotechnology and nanomedicine. Abstract : Crystalline nanoparticles of cellulose exhibit attractive properties as nanoscale carriers for bioactive molecules in nanobiotechnology and nanomedicine. For applications in imaging and drug delivery, surface charge is one of the most important factors affecting the performance of nanocarriers. However, current methods of preparation offer little flexibility for controlling the surface charge of cellulose nanocrystals, leading to compromised colloidal stability under physiological conditions. We report a synthesis method that results in nanocrystals with remarkably high carboxyl content (6.6 mmol g −1 ) and offers continuous control over surface charge without any adjustment to the reaction conditions. Six fractions of nanocrystals with various surface carboxyl contents were synthesized from a single sample of softwood pulp with carboxyl contents varying from 6.6 to 1.7 mmol g −1 and were fully characterized. The proposed method resulted in highly stable colloidal nanocrystals that did not aggregate when exposed to high salt concentrations or serum-containing media. Interactions of these fractions with four different tissue cell lines were investigated over a wide range of concentrations (50–300 μg mL −1 ). Darkfield hyperspectral imaging and confocal microscopy confirmed the uptake of nanocrystals by selected cell lines without any evidence of membrane damage or change in cell density; however a charge-dependent decrease in mitochondrial activity was observed for charge contents higher than 3.9 mmol g −1 . A high surface carboxyl content allowed for facile conjugation of fluorophores to the nanocrystals without compromising colloidal stability. The cellular uptake of fluoresceinamine-conjugated nanocrystals exhibited a time–dose dependent relationship and increased significantly with doubling of the surface charge.